3x(2x-1)-6x(7+x)=90

Simple and best practice solution for 3x(2x-1)-6x(7+x)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(2x-1)-6x(7+x)=90 equation:


Simplifying
3x(2x + -1) + -6x(7 + x) = 90

Reorder the terms:
3x(-1 + 2x) + -6x(7 + x) = 90
(-1 * 3x + 2x * 3x) + -6x(7 + x) = 90
(-3x + 6x2) + -6x(7 + x) = 90
-3x + 6x2 + (7 * -6x + x * -6x) = 90
-3x + 6x2 + (-42x + -6x2) = 90

Reorder the terms:
-3x + -42x + 6x2 + -6x2 = 90

Combine like terms: -3x + -42x = -45x
-45x + 6x2 + -6x2 = 90

Combine like terms: 6x2 + -6x2 = 0
-45x + 0 = 90
-45x = 90

Solving
-45x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-45'.
x = -2

Simplifying
x = -2

See similar equations:

| 4t^3-3t=0 | | 16y^2-18y-9=0 | | x^2-15x-216=0 | | 9x^3+45x^2-25x-125=0 | | .5(2y-1)-(.5-.2y)+1=0 | | x+6-5x=180 | | 5=-(2+6t)-t | | 7x+4x-6x=8x | | (3x+2)(5x^2-16x+12)=0 | | 59=50+(n-40)/4 | | 4(5x+4)=24(x-1) | | 2z+3=76 | | 5x-8=13++7(x-3) | | -11=14-2h | | 4(5y-2)+3(2y+6)=25(3y+2)-19y | | 3(3z+3)=5z-7 | | a^2+11a-126=0 | | 15c^2=48+48c | | 8x^2-55x-7= | | 6x^2-5xy+y^2= | | 2x-100=5x-100 | | 4x^3-24x^2-x+36=0 | | 6n^2+2n-5= | | .75(y-200)= | | 1.6(a-4)-.6=(.4-7) | | 0=-5x+20 | | 0=5x+20 | | 6.6x-1.7=4.9 | | 0.8x-7.1=0.1 | | 5r^2-17r-12=0 | | .6m-1.4=(3.5m+1.7)-(2.7m-3.4) | | 2+a=16-6a |

Equations solver categories